The protective role of MC1R in chromosome stability and centromeric integrity in melanocytes - Li, X; Mao, W; Chen, J; Goding, C; Et al. (Springer Nature, 2021)
Variants in the melanocortin-1 receptor (MC1R) gene, encoding a trimeric G-protein-coupled receptor and activated by α-melanocyte-stimulating hormone (α-MSH), are frequently associated with red or blonde hair, fair skin, freckling, and skin sensitivity to ultraviolet (UV) light. Several red hair color variants of MC1R are also associated with increased melanoma risk. MC1R variants affect melanoma risk independent of phenotype. Here, we demonstrated that MC1R is a critical factor in chromosome stability and centromere integrity in melanocytes. α-MSH/MC1R stimulation prevents melanocytes from UV radiation-induced damage of chromosome stability and centromere integrity. Mechanistic studies indicated that α-MSH/MC1R-controlled chromosome stability and centromeric integrity are mediated by microphthalmia-associated transcription factor (Mitf), a transcript factor needed for the α-MSH/MC1R signaling and a regulator in melanocyte development, viability, and pigment production. Mitf directly interacts with centromere proteins A in melanocytes. Given the connection among MC1R variants, red hair/fair skin phenotype, and melanoma development, these studies will help answer a question with clinical relevance “why red-haired individuals are so prone to developing melanoma”, and will lead to the identification of novel preventive and therapeutic strategies for melanomas, especially those with redheads.